Asuhan Keperawatan pada Pasien Dengan Asma di Panti Sosial Tresna Werdha Sabai Nan Aluih Sicincin Kabupaten Padang Pariaman - ROSMARCELINA TUMANGGOR; Sandra Dewi; Hasmita Hasmita; Armaita Armaita (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Asthma is a chronic respiratory disease characterized by inflammation and narrowing of the airways, leading to symptoms such as shortness of breath, cough, and wheezing. In older adults, this condition becomes more complex due to decreased lung function and comorbidities. Globally, asthma affects around 262 million people and causes approximately 455,000 deaths per year. In Indonesia, the prevalence is about 4.5%, while in West Sumatra it is around 1,5%. At PSTW Sabai Nan Aluih Sicincin, asthma ranks 7th among the 15 most common diseases in elderly residents. This study aimed to provide nursing care for an asthma patient at PSTW Sabai Nan Aluih Sicincin using a case study approach through the nursing process, including assessment, nursing diagnosis, intervention, implementation, evaluation, and documentation, based on interviews, observation, and physical examination. The results of the assessment on Mr. M showed complaints of shortness of breath, cough, wheezing, fatigue, sleep disturbance, and hearing impairment. The nursing diagnoses were ineffective breathing pattern, disturbed sleep pattern, and impaired sensory perception (hearing). After five days of intervention, the sleep disturbance was resolved, while the other two problems were partially resolved. In conclusion, comprehensive nursing care can help reduce asthma symptoms and improve the quality of life of elderly patients; however, long-term management and risk factor control are still required for optimal outcomes.